Electronic Restaurant Tax Transaction Data Monitoring System Implementation at The Regional Revenue Agency of North Minahasa District - Wagiu, Adisthya; Dilapanga, Abdul Rahman; Tarore, Steven (International Journal of Information Technology and Education, 2023)
Implementation of an electronic Restaurant Tax Transaction Data Monitoring System as a form of Restaurant tax monitoring is the latest policy implemented by the North Minahasa Regional Revenue Agency (Bapenda), aimed at increasing Regional Original Income (PAD) through increasing tax discipline. This research aims to evaluate the effectiveness and investigate the background to the implementation of the electronic Tax Transaction Data Monitoring System in the Bapenda of North Minahasa Regency. This research is qualitative with a descriptive approach. The data used consists of primary and secondary data. Data collection was carried out through interviews, observation, and documentation. Descriptive analysis is used by applying contribution and effectiveness ratio calculation formulas to evaluate the success of policies adopted by Bapenda. The research results show that the implementation of the electronic Tax Transaction Data Monitoring System was carried out in response to the tax payment policy with an online and self-assessment system. However, the effectiveness of this policy is not yet optimal because it does not meet the five implementation criteria. Some of the obstacles identified involve a lack of cooperation from taxpayers, a shortage of workers at Bapenda, interference with the electronic Tax Transaction Data Monitoring System equipment, and internet network problems. To overcome these obstacles, Bapenda took steps such as communicating again with electronic Tax Transaction Data Monitoring System technicians, conducting outreach, and giving awards to taxpayers.